واقع تطبيق استراتيجية التعليم القائم على المشروع من وجهة نظر أساتذة المواد الأدبية والشرعية والاجتماعية في مرحلة التعليم المتوسط (Revue El-Wahat pour les Recherches et les Etudes, 2022)
هدفت الدراسة الحالية التعرف على واقع تطبيق استراتيجية التعليم القائم على المشروع من وجهة نظر أساتذة المواد الأدبية والشرعية والاجتماعية. وقد تكونت عينة الدراسة من 43 أستاذ وأستاذة في مرحلة التعليم المتوسط. وتمثلت أداة الدراسة في استخدام استبيان موجه لعينة الدراسة معد من طرف الباحثة. وأسفرت نتائج الدراسة على أن أغلب الأساتذة يطبقون استراتيجية التعليم القائم على المشروع، وأن أكثرهم يطبقونها إلا عند زيارة المفتش أو المدير فقط. ومن جانب آخر فإنهم لا يستخدمونها كاستراتيجية في كل الدروس بل تستخدم في دروس محددة. ويقر أغلب الأساتذة بأن لهم كفايات معرفية عن هذه الاستراتيجية، وأن لها أهمية في العملية التعليمية التعلمية، كما يؤكدون على وجود صعوبات في تطبيقها.كلمات مفتاحية: استراتيجية التعليم القائم على المشروع، أساتذة المواد الأدبية والشرعية والاجتماعية، مرحلة التعليم المتوسط.  AbstractThe main objective of the present study was to identify the reality of implementation of project Based-teaching strategy from the point of view of the teachers of literary, legal and social subjects and foreign languages in the intermediate education stage in intermediate education. The basic study sample consisted of 43 male and female of teachers, The study tool consisted of using a questionnaire directed at the sample of the study prepared by the researcher. The results of the study included that most teachers apply the project strategy and most of them apply when visiting the inspector or the manager. On the other hand, they do not use it as a strategy in all lessons, but rather use it in specific lessons. Most of the teachers admit that they have sufficient knowledge’s of this strategy, and this strategy is important in the teaching-learning process, and they confirm that there are difficulties in implementing it.Keywords: project Based teaching strategy, teachers of literary, legal and social subjects, intermediate education stage.